Analisis Pelaksanaan Sistem Pengelolaan Limbah Medis di Rumah Sakit Daerah Kepulauan - Christin Andolo; Diana V. D. Doda; Lydia E. N. Tendean (Universitas Sam Ratulangi, 2024)
Abstract: In general, developing countries have not yet implemented optimal management of medical waste, which causes the accumulation of medical waste. Research on medical waste management in hospitals located in the Archipelago area is still lacking, so research like this needs to be carried out. This study aims to analyze the implementation of the medical waste management system at the Islands Regional Hospital. The research method used is a qualitative method with eight informants. The research results show that in terms of human resources, there is still a lack, especially for the medical waste management section, of budgetary and financial resources to facilitate the training of medical staff, cleaning staff, procurement and maintenance of infrastructure, and investment in better waste management technology. Inadequate medical waste management methods also affect the effectiveness of medical waste management itself and can lead to an increasing amount of medical waste. The amount of medical waste generated can affect the capacity and method of treatment required. The observation results show that there are problems in sorting and containerizing medical waste where the trash for non-medical waste has been mixed with medical waste. In the temporary storage area, medical waste has accumulated a lot and has not been processed or recycled. Treatment of medical waste uses an autoclave and also incinerates medical waste manually. This is done because the incinerator is not functioning optimally. The conclusion of this study is that the medical waste management system is not yet optimal. It is hoped that the hospital, as well as health workers and cleaners, can implement an optimal medical waste management system to avoid things that can cause health problems, environmental disturbances, and ecosystem disturbances. Keywords: Waste, Medical, Non-Medical, Management. Abstrak : Secara umum pada negara berkembang belum menerapkan pengelolaan limbah medis yang optimal sehingga menyebabkan penumpukan limbah medis. Penelitian tentang pengelolaan limbah medis di Rumah Sakit yang berada di daerah Kepulauan masih sangat kurang sehingga penelitian seperti ini perlu untuk dilakuan. Penelitian ini bertujuan untuk menganalisis pelaksanaan sistem pengelolaan limbah medis di Rumah Sakit Daerah Kepulauan. Metode penelitian yang digunakan metode kualitatif dengan jumlah informan 8 orang. Hasil penelitian menunjukkan bahwa dari segi sumber daya manusia masih kurang khususnya untuk bagian pengelolaan limbah medis, kurangnya sumber anggaran dan keuangan untuk memfasilitasi pelatihan tenaga medis, petugas kebersihan, pengadaan, perawatan sarana prasarana, serta investasi dalam teknologi pengelolaan limbah yang lebih baik. Metode pengelolaan limbah medis yang kurang memadai juga berpengaruh terhadap efektivitas pengelolaan limbah medis itu sendiri serta dapat menyebabkan jumlah limbah medis yang semakin banyak. Jumlah limbah medis dihasilkan dapat mempengaruhi kapasitas dan metode pengolahan yang dibutuhkan. Hasil observasi menunjukan bahwa adanya masalah dalam pemilahan dan pewadahan limbah medis, dimana tempat sampah untuk limbah non medis sudah tercamur dengan limbah medis . Di tempat penyimpanan sementara limbah medis sudah sangat menumpuk dan belum di olah ataupun di daur ulang. Pengolahan limbah medis menggunakan autoclave dan juga melakukan pembakaran limbah medis secara manual hal ini dilakukan karena incinerator belum berfungsi secara optimal. Kesimpulan penelitian ini yaitu belum optimalnya sistem pengelolaan limbah medis. Diharapkan kepada pihak rumah sakit dan juga petugas kesehatan serta petugas kebersihan dapat menerapkan sistem pengelolaan limbah medis secara optimal untuk menghindari hal-hal yang dapat menyebabkan gangguan kesehatan, gangguan lingkungan dan juga gangguan ekosistem. Kata Kunci : Limbah, Medis, Non Medis, Pengelolaan.